1997
DOI: 10.1177/096032719701600703
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of glutathione S-transferase M1 deletion in smokers with emphysema and lung cancer

Abstract: 1 Genetic variation at the glutathione S-transferase M1 locus (GSTM1) has been associated with a number of apparently unrelated cancers, including lung cancer. Emphysema is a common lung disease often found concomitant with lung cancer. Both emphysema and lung cancer may result from chemical and oxidative damage caused by reactive species present in cigarette smoke or released from neutrophils recruited follow ing cigarette smoke induced injury. GSTM1 may protect against such damage through detoxifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
2
4

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(62 citation statements)
references
References 13 publications
4
52
2
4
Order By: Relevance
“…The genetic factors are supposed to be related to this individual susceptibility. Recently, genetic polymorphism of cytochrome P450 [22], microsomal epoxide hydrolase [23], glutathione S-transferase M1 [24], tumour necrosis factor-a [25], and glutathione S-transferase P1 [26] were suggested to have an association with emphysema or COPD.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic factors are supposed to be related to this individual susceptibility. Recently, genetic polymorphism of cytochrome P450 [22], microsomal epoxide hydrolase [23], glutathione S-transferase M1 [24], tumour necrosis factor-a [25], and glutathione S-transferase P1 [26] were suggested to have an association with emphysema or COPD.…”
Section: Discussionmentioning
confidence: 99%
“…The association between GSTM1 gene and COPD has been reported in the past in several populations, including cohorts of Caucasian patients (34,35). The connection between GSTM1 gene and COPD should be considered on the basis that both lung cancer and COPD have a causative relationship with smoke exposure.…”
Section: Cyp1a1(m1)/gstm1(-)/gstt1(+) and Cyp1a1(wt)/gstm1(+)/gstt1(-)]mentioning
confidence: 99%
“…Nevertheless, it is still a matter of discussion whether GSTM1 polymorphism alone could confer an increased risk of lung cancer. Indeed, several recent studies reported significant differences in the polymorphism frequency between lung cancer patients and a control population, while others failed to show any connection (Harrison et al 1997;Sun et al 1997). GSTT1 and GSTP1 are members of the family characterized by a high frequency of polymorphism (Pastore et al 2003;Su et al 2003).…”
Section: Multidrug Resistance Associated Protein -Mrp (Mrp1)mentioning
confidence: 99%